If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17 + 2(2n + -12) = 1 Reorder the terms: 17 + 2(-12 + 2n) = 1 17 + (-12 * 2 + 2n * 2) = 1 17 + (-24 + 4n) = 1 Combine like terms: 17 + -24 = -7 -7 + 4n = 1 Solving -7 + 4n = 1 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 4n = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 4n = 1 + 7 4n = 1 + 7 Combine like terms: 1 + 7 = 8 4n = 8 Divide each side by '4'. n = 2 Simplifying n = 2
| -6m+4=2 | | -2+3(-1)=-(-1+6) | | -10y+18=-(5y-7)+6y | | 12*-3.8-10=4*-3.8-32-3*-3.8 | | 16-8n+3+2n=45 | | 2x+7=6x-14 | | .5x-2=8 | | 9m-15=66 | | 4(2p-2)=3(2p+4) | | -3(2-1x)=2x-9 | | 2=-2y+6/13 | | 10y=-5x-15 | | 11x=-42 | | 3+log[4](x+6)=4 | | 0.12x^2-0.72x-0.137=0 | | 100x+100x^2-45=0 | | 2014-1952+-7abc+18=62 | | -2(3x-4)=-(2x-2) | | 0.12x^2+-0.72x+-0.137=0 | | 20x-24=2x | | -11=7-1x | | 45g+7=-6 | | x^3-(2x^2)+1.25x-0.25=0 | | 1952-7abc+18=62 | | 2+2k=8k+3-6k | | x^3-(2x^2)+1.5x-0.25=0 | | 5n-8=n+27 | | [9(y+5)-17]-[3(y-4)+3]= | | 5x-3+7x=45 | | 2+2k=8k+3-6 | | 2(x-2)=3x-4x+5 | | 2x+10=6x-4 |